There's a lithium battery in your future. (December 2019) - Berkowitz, Rachel; Aurbach, Doron
Abstract : Battery technology has come a long way since September 1899, when Ferdinand Porsche's electric powered car won its first road race. The "Egger-Lohner electric C.2 Phaeton" carried a Tudor brand lead-acid battery that weighed 500 kg and propelled the 1350-kg vehicle with 3 hp (2.2 kW for 3–5 h) for 80 km.